Edukasi Dan Simulasi Keterampilan Perawatan Luka Ringan Bagi Kader Usaha Kesehatan Sekolah (UKS) Di SDN 1 Blang Mangat Kota Lhokseumawe - Sulaiman; Syahabuddin; Ismailinar; Said Taufiq; Fitriani Agustina (JEUMPA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract Injury events cause 7% of deaths worldwide, and this figure is expected to continue to increase. In addition, injuries and trauma result in approximately a 16% reduction in life expectancy due to disability (Disability Adjusted Life Year/DALY). Of these events, 12.8% are due to unintentional causes, and 3.2% are due to intentional injuries. Traffic accident-related injuries rank tenth as a cause of death and rank first among all types of injuries worldwide. The target audience of this Community Partnership Program is the UKS cadres at SDN 1 Blang Mangat. The goal of this activity is to improve student health and enhance wound care skills for UKS cadres at SDN 1 Blang Mangat, Lhokseumawe City. The problem encountered is that the students' skills in providing basic wound care are not yet effective, and the coaching of UKS cadres in performing basic wound care is not optimal. The methods used in this activity are education and simulation regarding wound concepts, the wound healing process, infections in wound care, and wound care techniques. The expected outcomes from the implementation of this PKM are increased knowledge of UKS cadres about wound concepts, the wound healing process, infections in wound care, and wound care techniques. The UKS cadres' skills in applying wound care techniques are also expected to improve. Keywords: UKS cadre, Education, Wound care